Desenvolvimento e avaliação de um jogo para o ensino do método de criatividade sinética - Bendotti, Vanessa (2019)
Creativity is one of the most anticipated skills of future engineers. With the evolution of technology, workers will have to become more creative to take advantage of the changes. To stimulate creativity, there is the Creativity Methods (MC) used in universities to stimulate students' creative thinking and prepare them for the job market. The objectives of MCs are to facilitate the expression and evolution of some creative processes, be it individual, group or organizational. The Synectics method, created by George Prince and Willian Gordon, in the 1950s, involves preconscious analogies and mechanisms of the human being, being able to be used in the solution of general and specific problems, but the method is little explored in Brazil, especially in Brazil. academia. An effective way to learn and stimulate creativity with MC and the Synectics method is through the use of games, which are used universally to simulate real situations, in which the student from quick observations, has instant feedback of their actions. Thus, the objective of the present work is the development and evaluation of a game to aid in the creative development of the student, using the Synectics method as a base. The research used, as a methodological approach, the Design Science Research, methodology that is oriented to the design, development of an artifact (i.e. the game), demonstration, evaluation, and communication of the results found. The resulting game was applied through mini courses, lasting four hours, to 60 students, of the mechanical engineering course, the Universidade Tecnológica Federal do Paraná (UTFPR) and UniBrasil. At the first moment, the students contacted the method without using the game and answered a questionnaire related to the method. Subsequently, the students received another problem to solve with the method, using the game as an auxiliary methodology. At this stage the students had thirty minutes to solve the problem, they had to present a scheme where they showed the use of the method and in the end, each team was audited by a member of the other team. The team with the highest score would win the game. In the end, the students individually answered four questionnaires, the first one referring to the student profile, the second related to the methodology of the game, the third about the motivation during the activity and the last questionnaire, again, related to the method. Through the questionnaires, it was possible to observe that the method is difficult to understand when not put into practice. The game was well evaluated concerning attention, relevance, confidence, satisfaction, immersion, social interaction and fun, contributing to student learning. The motivation questionnaire showed that UTFPR students were more stimulated to perform the activity than the UniBrasil students, due to the interest of each group. In this way, the game proved to be a good auxiliary teaching tool in the universities, helping to improve the research, selection, organization and information communication skills in which students were able to contextually assimilate the Synectics method and be creative in solving problems.